THE USE OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) METHOD TO IMPROVE STUDENTS’ READING COMPREHENSION - Prajogo, M.Pd., Sigit (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
In general, most of the students of senior high school have difficulties in comprehending texts. The objective of this research was to investigate the use of Cooperative Integrated Reading and Composition (CIRC) method to improve students’ reading comprehension. The participants of this research were 32 students of grade XI of Social Science (XI IPS 1) of SMA 2 Blitar. This research was a classroom action research which was done in two cycles. The data of this research were collected by conducting observation, interview, documentation, and test with the criteria of minimum mastery (KKM) of 76. The result showed that that the students successfully met the criteria of minimum mastery. It was indicated from the improvement of the students’ mean score from 74.38 in Cycle 1 to 81.41 in Cycle 2. It was also found that the students’ activity was delightful in the class thanks to the method. In conclusion, CIRC method was found beneficial to improve the students’ reading comprehension, and enhance the learning process of reading.